Effectiveness and User Satisfaction of Electronic Medical Records in Indonesia Private Hospital - Kurniawan, Abdul Latif; Arini, Merita (South Eastern European Journal of Public Health, 2024)
The implementation of Electronic Medical Records (EMRs) in hospitals offers numerous benefits, including enhanced healthcare quality and safety, improved access to information, increased healthcare professional productivity, and reduced healthcare costs. Despite these advantages, the effectiveness and user satisfaction of EMRs can be hindered by challenges such as high implementation costs, user resistance, and complex integration processes. This study aims to investigate the effectiveness and user satisfaction of EMRs in the inpatient room of Siti Khodijah Muhammadiyah Hospital Branch of Sepanjang. This study employed a cross-sectional approach using validated questionnaire. This survey involved 86 healthcare workers (HCWs) in November 2023. The Technology Acceptance Model (TAM) was applied to assess the effectiveness of EMR implementation, while the ServQual method measured user satisfaction. This study revealed that the relevance (P = 0.001) and accuracy (P = 0.001) of the EMR system are critical factors that significantly influence HCWs’ satisfaction. Users who found the EMR system relevant and accurate reported higher levels of satisfaction. However, aspects such as the timeliness (P = 0.404), completeness of data (P = 0.053) and support system (P = 0.670), while important, did not show a statistically significant impact on user satisfaction. Ensuring the relevance and accuracy of the system is essential to enhance user satisfaction. Practically, improving these aspects can lead to better HCW engagement with EMRs, and future research should explore strategies to address the non-significant factors for a comprehensive understanding of EMR effectiveness.